Exploring Types of Parental Involvement at Secondary Public Schools in Baku - Monsumova, Tinatin (ADA University, 2021)
The purpose of this study was to investigate how parental involvement is perceived by school teachers, parents, and school principals. Additionally, the study aimed to explore the types of parental involvement fostered by teachers and school principals. The research questions were designed around the above-mentioned study purposes: 1. “How is parental involvement defined by teachers, parents, and school principals in Baku secondary public schools?” 2. “What types of parental involvement are fostered by teachers and school principals in Baku secondary public schools?” Types of parental involvement were investigated using a qualitative research approach based on Epstein’s (2009) theoretical framework of six types of parental involvement. The study was conducted in two public secondary schools of Baku, which were selected through convenience sampling. Accordingly, the data were collected employing qualitative research methodologies with the help of semi-structured individual interviews with teachers, parents, and school principals. Generally, 34 participants were selected through simple random sampling. The study used two cycles of coding to analyze the data. Initially, open coding was used, and in the second phase, axial coding was employed. The findings of the study showed that the most common type of parental involvement in the sampled schools is communication, which is consistent with Epstein’s framework (2009). Also, the study found several practices specific to the types of parental involvement introduced in Epstein’s framework. However, the findings show that the participants were vaguely aware of the types of parental involvement.
Keywords: Education; Schools, Public -- Azerbaijan.; Schools, Public -- Parental involvement.; Epstein’s framework.